Evaluation of the Brief Multidimensional Students' Life Satisfaction Scale in a Diverse Sample of Rural Early Adolescents. (April 2022) - Pittman, Sarah K.; Valois, Robert F.; Farrell, Albert D.
Although life satisfaction has been associated with maladjustment and adverse experiences among adolescents, few validated measures of life satisfaction have been evaluated for use with diverse populations. The Brief Multidimensional Students' Life Satisfaction Scale (BMSLSS) is a promising measure that has been validated in samples of White and Black adolescents. This study used an item response theory approach to evaluate its psychometric properties in a diverse rural sample of early adolescents and its concurrent associations with other measures of youth adjustment. Support was found for partial invariance across sex and racial and ethnic identities. Scores on the BMSLSS were also correlated with measures of youth adjustment. However, the strength of these correlations differed for adolescents of different racial and ethnic identities. Findings suggest that the BMSLSS is a psychometrically sound measure for assessing life satisfaction in diverse samples of adolescents and highlights the importance of assessing invariance across racial and ethnic groups.